Live high, train low – influence on resting and post‐exercise hepcidin levels. (31st March 2016) - Govus, A. D.; Peeling, P.; Abbiss, C. R.; Lawler, N. G.; Swinkels, D. W.; Laarakkers, C. M.; Thompson, K. G.; Peiffer, J. J.; Gore, C. J.; Garvican‐Lewis, L. A.
Abstract : The post‐exercise hepcidin response during prolonged (>2 weeks) hypoxic exposure is not well understood. We compared plasma hepcidin levels 3 h after exercise [6 × 1000 m at 90% of maximal aerobic running velocity ( v VO2max )] performed in normoxia and normobaric hypoxia (3000 m simulate altitude) 1 week before, and during 14 days of normobaric hypoxia [196.2 ± 25.6 h (median: 200.8 h; range: 154.3–234.8 h) at 3000 m simulated altitude] in 10 well‐trained distance runners (six males, four females). Venous blood was also analyzed for hepcidin after 2 days of normobaric hypoxia. Hemoglobin mass (Hbmass ) was measured via CO rebreathing 1 week before and after 14 days of hypoxia. Hepcidin was suppressed after 2 (Cohen's d  = −2.3, 95% confidence interval: [−2.9, −1.6]) and 14 days of normobaric hypoxia ( d  = −1.6 [−2.6, −0.6]). Hepcidin increased from baseline, 3 h post‐exercise in normoxia ( d  = 0.8 [0.2, 1.3]) and hypoxia ( d  = 0.6 [0.3, 1.0]), both before and after exposure (normoxia: d  = 0.7 [0.3, 1.2]; hypoxia: d  = 1.3 [0.4, 2.3]). In conclusion, 2 weeks of normobaric hypoxia suppressed resting hepcidin levels, but did not alter the post‐exercise response in either normoxia or hypoxia, compared with the pre‐exposure response.